La gran represión : Los aǫs de plomo de la posguerra (1939-1948) / Manuel Álvaro Dueąs, Francisco Espinosa Maestre y José María García Márquez ; Mirta Nuęz Díaz-Barlat (coordinadora) - Espinosa Maestre, FranciscoGarcía Márquez, José MaríaNúęz Díaz-Balart, Mirta; Dueąs, Manuel Álvaro (Con Franco vivíamos peor; 8)
Bibliogr.: pp. 459-488. Índice onomástico